Effect of priming on Muslim personality - Badi, Jamal Ahmed Bashier (s.n, 2012)
This study is set to investigate whether awareness of been primed leads to contrast effects following mind-set primes of the Muslims' which is reflected in their behaviors from all sets i.e. religious affiliations